2011
DOI: 10.1007/s00240-011-0401-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antiurolithic effect and the possible mechanisms of Desmodium styracifolium and Pyrrosiae petiolosa in rats

Abstract: Chinese herbs Desmodium styracifolium (Ds) and Pyrrosiae petiolosa (Pp) have been widely used to treat urolithiasis with few side effects in traditional Chinese medicine (TCM). In vitro crystallization study has confirmed their prophylaxis of Calcium oxalate (CaO( x )) stones formation. However, little is known on their possible mechanisms in vivo. In the present study, we proposed to systematically evaluate their antilithic effects and clarify the underlying mechanism of Ds and Pp using a rat nephrolithiasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…ex Diels) Ching, have been used to substitute for medicinal Pyrrosia. These substitutes have not been recorded in the Chinese pharmacopoeia, however, many of them have a wide circulation in the market and display good clinical efficacy (Mi et al, 2012). For pharmaceutical workers, it is difficult to distinguish P. petiolosa from P. davidii, especially from their parts (Shi et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…ex Diels) Ching, have been used to substitute for medicinal Pyrrosia. These substitutes have not been recorded in the Chinese pharmacopoeia, however, many of them have a wide circulation in the market and display good clinical efficacy (Mi et al, 2012). For pharmaceutical workers, it is difficult to distinguish P. petiolosa from P. davidii, especially from their parts (Shi et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…In vitro crystallization study has confirmed the prophylactic effect of D. styracifolium in the formation of calcium oxalate crystals [8,9]. Further in vivo study subsequently demonstrated that the aqueous extracts from D. styracifolium inhibited CaOx stone formation by rising urinary citrate excretion, decreasing urinary calcium, diuresis, and enhancing antioxidative effects in rats [10]. We have also previously reported the antiurolithic and antioxidant activities of D. styracifolium aqueous crude extract in vivo, which is consistent with the above [11,12].…”
Section: Introductionmentioning
confidence: 64%
“…In view of the traditional medical uses of D. styracifolium in urolithiasis and the previous studies of D. styracifolium crude extract showing the antilithic activity in rats [8][9][10][11][12], we were motivated to further study the extracts from different polarity fractions, including Fr. CH, Fr.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plant extracts with strong antioxidant potential have shown anti-urolithiatic effects [4]. Understanding the pathophysiology of renal calculi formation and the effect of antioxidants against the process have resulted in the idea of using phyto-compounds as potential therapy for the disease [5].…”
Section: Introductionmentioning
confidence: 99%